PENGARUH PENGGUNAAN E-LKPD TERHADAP HASIL BELAJAR MATEMATIKA SEKOLAH DASAR - Yunni Arnidha; Norma Yunaini; Agata Alvi Dwi Tantri (Jurnal Muara Pendidikan, 2023)
This study aimed to determine the effect of using the E-LKPD on elementary school mathematics learning outcomes. This research is motivated by technological developments and the low utilization of E-LKPD in mathematics learning. The research method used is the quantitative method "non-equivalent control group design". This research was conducted in two elementary schools. The population in this study were fifth-grade students and the sample used was 15 students from two schools. The research instrument is E-LKPD. Data collection techniques using observation techniques, documentation, and scores. Data were analyzed using the prerequisite test with three stages, namely, normality test, homogeneity test, and t-test. The results showed a significant effect on elementary school mathematics learning outcomes, where the average score of students' learning outcomes after using the E-LKPD increased by 12%. The results of the hypothesis test using the paired sample t-test showed that both classes after being treated obtained tcount > ttable but the tcount value in the experimental class was greater than the tcount value in the control class or 7.048 > 6.569, then Ha was accepted and Ho was rejected. This means that the use of E-LKPD can affect the learning outcomes of elementary school mathematics.